Augmented reality surgical navigation system based on the spatial drift compensation method for glioma resection surgery. Issue 6 (13th April 2022) - Zhou, Zeyang; Yang, Zhiyong; Jiang, Shan; Zhuo, Jie; Zhu, Tao; Ma, Shixing
Abstract: Background: The number of patients who suffer from glioma has been increasing, and this malignancy is a serious threat to human health. The mainstream treatment for glioma is surgical resection; therefore, accurate resection can improve postoperative patient recovery. Purpose: Many studies have investigated surgical navigation guided by mixed reality, with good outcomes. However, the limitations of mixed reality, such as spatial drift caused by environmental changes, limit its clinical application. Therefore, we present a mixed reality surgical navigation system for glioma resection. Preoperative information can be fused precisely with the real patient with the spatial compensation method to achieve clinically suitable accuracy. Methods: A head‐mounted device was used to display virtual information, and a markerless spatial registration method was applied to precisely align the virtual anatomy with the real patient preoperatively. High‐accuracy preoperative and intraoperative movement and spatial drift compensation methods were used to increase the positional accuracy of the mixed reality‐guided glioma resection system when the patient's head is fixed to the bed frame. Several experiments were designed to validate the accuracy and efficacy of this system. Results: Phantom experiments were performed to test the efficacy and accuracy of this system under ideal conditions, and clinical tests were conducted to assess the performance of this system in clinical application. The accuracy of spatial registration was 1.18 mm in the phantom experiments and 1.86 mm in the clinical application. Conclusions: Herein, we present a mixed reality‐based multimodality‐fused surgical navigation system for assisting surgeons in intuitively identifying the glioma boundary intraoperatively. The experimental results indicate that this system has suitable accuracy and efficacy for clinical usage.